DESIGN AND MANUFACTURING DEVICE MOBILITY LOAD MOTION SHIELDING PARAFFIN RADIATION PROTECTION SYSTEM FACILITY TEST IN VITRO IN VIVO - Widarto Widarto (Indonesian Journal of Physics and Nuclear Applications, 2019)
Practical work at PSTA-BATAN to find paraffin design and the design of mobile devices with Monte Carlo N Particle (MCNP) software. The method used is to determine the paraffin design and calculate the volume of paraffin. The resulting intact writing that modeled with the MCNP. Shielding is required to absorb the leaking radiation until the 20 mSv / year Dose Limit Value for radiation workers is met. The material used is paraffin. Calculation is done by using MCNPX calculation facility with tariff of 10,42 μSv / hour. The paraffin design criteria are built on recommendations from Indonesian Journal of Physics and Nuclear Applications Volume 1, Number 1, February 2016. Some of the above-standard methods are overcome with the protection aspects of distance and radiation time. Paraffin used is made of hydrocarbons suitable for strengthening shielding structures and for absorbing gamma radiation.